The Influence Of Financial Literacy And Financial Self Efficacy On Risky Credit Behavior In The Use Of Paylater Among Students(case study of FEB students at Bandar Lampung University) - Dhani Ahmad Kautsar; Defrizal (Cita konsultindo, 2025)
This study aims to demonstrate the influence of financial literacy and financial self-efficacy on credit risk in the use of PayLater services among students. This research employs a quantitative approach and the analysis technique used is Multiple Linear Regression with a sample of 91 students. This analysis states that financial literacy has a significant inverse relationship with credit risk, which means that increased financial literacy results in a decrease in credit risk levels when using pay later. Additionally, financial self-efficacy also has an inverse relationship with risky credit behavior, indicating that self-confidence in managing finances can reduce risky credit behavior. This research implies that efforts to improve financial literacy and strengthen financial self-efficacy need to be undertaken, especially among students, in order to minimize the detrimental impacts of risky credit behavior in the use of pay later.